High-resolution multi-modal imaging of sub-cellular structures with low numerical aperture objective - Somaiyeh Khoubafarin; Peuli Nath; Saloni Malla; Durgesh Desai; William D Gorgas; Amit K Tiwari; Aniruddha Ray (JPhys Photonics)
Imaging of subcellular structures, which underpins many of the advances in biological and medical sciences, requires microscopes with high numerical aperture (N.A.) objectives which are costly, complex, requires oil immersion and have very limited field-of-view, typically covering a handful of cells. Here, we leverage a low N.A. objective to simultaneously capture scattering, phase, and fluorescence images of subcellular structures in breast cancer cells (BT-20) and observe nanoparticle uptake, with sub-diffraction-limited resolution (<400 nm with a 0.25 N.A. objective) utilizing a 2-dimensional (2-D) microlens substrate. High resolution labeled and label-free images of subcellular components is made possible by implementing a specific configuration, wherein the sample is placed in close proximity to the microlens substrate, which results in efficient collection of the rapidly decaying evanescent waves that contains the high frequency information, thereby improving resolution and the light capture efficiency. The microlens-assisted imaging provides an easy-to-implement and cost-effective means of drastically improving the resolution of any microscope with low N.A. objective lenses, paving the way for the development of affordable, portable multi-modal imaging systems with high-resolution imaging capabilities. This technology has broad implications for various fields and could democratize access to high-quality microscopy, particularly for application in resource-limited settings.